Greening the hospitality industry in the developing world: Analysis of the drivers and barriers. (16th November 2018) - Mzembe, Andrew Ngawenja; Melissen, Frans; Novakovic, Yvonne
Abstract: The implementation of sustainability agendas in the tourism and hospitality industry in developing countries has received little scholarly attention. Working to fill this gap, this paper provides a holistic analysis of the drivers of, and barriers to, sustainability initiatives in the Malawian hospitality industry. Drawing insights from the resource‐based view and institutional theory, it highlights that tensions between global and local norms and values are as important as tensions between internal organizational factors and the isomorphic forces within the organizational fields for implementing sustainability agendas. The paper further reveals the mediating role played by firm size and ownership. It, thus, makes a contribution to the understanding of the role of business in society by focusing on the complex dynamics associated with the adoption of sustainability agendas in an under‐researched context, and demonstrating how tensions between internal organizational factors and local societal expectations within the host countries can shape the nature and focus of the sustainability agenda itself.